Pre- and post-chemotherapy spermatogenesis in male patients with malignant bone and soft tissue tumors - Takeshima, Teppei; Mimura, Noboru; Aoki, Shun; Saito, Tomoki; Karibe, Jurii; Usui, Kimitsugu; Kuroda, Shinnosuke; Komeya, Mitsuru; Yumura, Yasushi (Frontiers in Pharmacology, 2023)
Introduction: Malignant bone and soft tissue tumors, commonly called sarcomas, predominantly originate in bone and soft tissues and typically affect individuals at a younger age. Following the resection of the primary tumor, treatment often necessitates radiation therapy and gonadotoxic chemotherapy, the specifics of which depend on the disease’s stage Conversely, there is a notable concern regarding the potential loss of fertility due to these treatments. Consequently, it is recommended that men consider sperm cryopreservation before initiating treatment. This study aims to assess spermatogenesis in male patients diagnosed with malignant bone and soft tissue tumors before and after chemotherapy. Methods: This study involved 34 male patients diagnosed with malignant bone and soft tissue tumors and subsequently underwent sperm cryopreservation before initiating treatment. Medical records included details about the primary disease, age, marital status at presentation, semen analysis results, treatment regimen and number of courses, post-treatment semen analysis, renewal status and outcomes. Results: The mean age at the time of sperm cryopreservation was 22.8 years. The median semen volume was 2.5 mL, sperm concentration was 32.6 million/ml, and sperm motility was 38.5%. Following chemotherapy, semen analysis was conducted on 12 patients, with ifosfamide being the predominant drug used in all cases. Among these 12 patients, eight retained viable spermatozoa, and two successfully achieved spontaneous pregnancies resulting in live births. In one of the remaining four cases where no sperm were detected in ejaculate, a live birth was achieved through intracytoplasmic sperm injection using cryopreserved sperm. Discussion: While ifosfamide, the primary chemotherapy drug for patients with malignant bone and soft tissue tumors, was associated with severe impairments in spermatogenesis, recovery of spermatogenesis was observed in many cases. However, there were instances of prolonged azoospermia. Even in such cases, assisted reproduction using cryopreserved sperm remained viable for achieving parenthood. In light of these findings, offering patients the opportunity for fertility preservation is advisable.